(untitled) (Revista Puertorriqueña de Psicologia, 2016)
Both the general public and the psychological profession share many fallacies and misconceptions about parapsychology. In this paper, written for Puerto Rican psychologists, the authors discuss five fallacies about parapsychology. These are: (1) There are no scientific or rigorous studies in parapsychology; (2) parapsychologists are individuals with psychic abilities; (3) occultism and spiritism are an integral part of parapsychology; (4) there are valid and reliable techniques for the development of psychic abilities; (5) parapsychology has little or no relevance for the psychologist. Although the authors recognize the problems of parapsychoogy, they argue that this field can be useful to open the minds of psychologists to the complexities of the scientific endeavor and of human experience.